Match running performance characterizing the most elite soccer match-play - Toni Modric; Sime Versic; Ryland Morgans; Damir Sekulic (Termedia Publishing House, 2023)
In order to identify match running performance (MRP) characterizing the most elite soccer matchplay, this study aimed to examine position-specific differences in the MRP of players competing in "big five" (BFLTs) and "non-big five" league teams (N-BFLTs). The data were obtained from 24 teams (BFLTs; n = 14, N-BFLTs; n = 10) during the UEFA Champions League (UCL) matches (n = 20) in the 2020/21 season using a semiautomatic video system. The differences in MRP between BFLTs and N-BFLTs, while controlling for contextual factors, were examined using linear mixed model. No differences in overall MRP between fullbacks, central midfielders, wide midfielders and forwards from BFLTs and their peers from N-BFLTs were found, while only central defenders from BFLTs covered more high-intensity running than central defenders from BFLTs (moderate effects size). For players on all playing positions from BFLTs, total- and low-intensity distance covered were lower in offensive phase of game and greater in defensive phase of game compared to their peers from N-BFLTs (all large effect sizes). This study demonstrated that the most elite match-play in soccer is characterized by increased efforts in defensive phase of game, and decreased efforts in offensive phase of game. Soccer training programmes should be adapted accordingly.